A study of hardcoat anodizing on PM Al-Mg composite - Mohd Nasuha Ab. Halim (University Malaysia Perlis, 2009)
This research is being conducted to investigate an effect occurring on anodizing process on powder metallurgy Aluminium-Magnesium (PM Al-Mg) composite. Composite materials are fabricated by using powder metallurgy method which is consist of mixing, compaction, and sintering. After fabrication, composite materials are undergoes to anodizing processes by using sulphuric acid as an electrolyte on 3°C. Anodizing processes is done using 90 volt of electrical current and 30 Ampere of DC current. This research is covered about percentage of sulphuric acid concentration as an electrolyte and duration of anodizing processes. Sulphuric acid concentration that used in this project are being divided into 4 classes which is 5%, 10%, 15% and 20%, meanwhile anodizing processes duration is raging from 10, 20, 30, 40, 50 and 60 minutes. A major objective in this project is to find the best solution among parameter used in this project.